2014
DOI: 10.1016/j.ajhg.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Carbonic Anhydrase VA Deficiency Resulting from CA5A Alterations Presents with Hyperammonemia in Early Childhood

Abstract: Four children in three unrelated families (one consanguineous) presented with lethargy, hyperlactatemia, and hyperammonemia of unexplained origin during the neonatal period and early childhood. We identified and validated three different CA5A alterations, including a homozygous missense mutation (c.697T>C) in two siblings, a homozygous splice site mutation (c.555G>A) leading to skipping of exon 4, and a homozygous 4 kb deletion of exon 6. The deleterious nature of the homozygous mutation c.697T>C (p.Ser233Pro)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 25 publications
6
80
1
Order By: Relevance
“…Trio whole exome sequencing (WES) was carried out to exclude any novel genetic defects in the biotin pathway, and included analyses for any mutations in the mitochondrial carbonic anhydrase VA (CA5A) gene which presents with MCD phenotype (Karnebeek et al 2014) but all tests were non-contributory.…”
Section: Case Reportmentioning
confidence: 99%
“…Trio whole exome sequencing (WES) was carried out to exclude any novel genetic defects in the biotin pathway, and included analyses for any mutations in the mitochondrial carbonic anhydrase VA (CA5A) gene which presents with MCD phenotype (Karnebeek et al 2014) but all tests were non-contributory.…”
Section: Case Reportmentioning
confidence: 99%
“…The first discovery was a homozygous missense variant in CA5A (Mendelian Inheritance in Man [MIM] number 114761), encoding mitochondrial carbonic anhydrase VA, which is pivotal to the function of mitochondrial enzymes. 17 Our group reported that a deficiency in this enzyme causes neonatal hyperammonemia, hyperlactatemia, and hypoglycemia. 17 Such a deficiency is amenable to treatment with carglumic acid and an emergency protocol, which can prevent irreversible neurologic sequelae.…”
Section: Resultsmentioning
confidence: 96%
“…17 Our group reported that a deficiency in this enzyme causes neonatal hyperammonemia, hyperlactatemia, and hypoglycemia. 17 Such a deficiency is amenable to treatment with carglumic acid and an emergency protocol, which can prevent irreversible neurologic sequelae. We added this condition to the two-tiered diagnostic algorithm and interactive tool at Treatable ID.org (freely available as native and Web applications at www.treatable-id.org) to support clinicians in early identification.…”
Section: Resultsmentioning
confidence: 96%
“…Patients with a mutation in CA12 exhibit hyponatremia and hyperchlorhydria [34]. Individuals with homozygous mutation in CA5a are reported to have lethargy, hyperlactatemia, and hyperammonemia during the neonatal period and early childhood [35]. CA6 is initially described as a gustatory protein and highly expressed in the salivary and mammary glands.…”
Section: Introductionmentioning
confidence: 99%